2017
DOI: 10.1007/s00408-017-9981-9
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Positive Airway Pressure Adherence In Patients with Obstructive Sleep Apnea & Symptomatic BPH

Abstract: Purpose To determine the short-term and long-term adherence rates with continuous positive airway pressure (CPAP) therapy in sleep apnea patients with benign prostatic hyperplasia (BPH) compared to matched controls. Methods A case-control retrospective analysis was performed in a veterans affairs hospital. All symptomatic patients with BPH (n = 107) ever started on CPAP therapy between 2006 and 2012 were compared with controls matched for severity of sleep apnea (AHI). Adherence measures were obtained at the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Further, Irer et al found that when with men with OSA and LUTS consistently used CPAP, nighttime urine volumes decreased from 547 to 96 cc (P<0.001) and the frequency of nocturia decreased from 2.1 to 0.5 bathroom trips at night (22). Fortunately, the presence of LUTS has not been found to decrease adherence to CPAP use when compared to men without LUTS (26).…”
Section: Sleep and Lower Urinary Tract Symptomsmentioning
confidence: 99%
“…Further, Irer et al found that when with men with OSA and LUTS consistently used CPAP, nighttime urine volumes decreased from 547 to 96 cc (P<0.001) and the frequency of nocturia decreased from 2.1 to 0.5 bathroom trips at night (22). Fortunately, the presence of LUTS has not been found to decrease adherence to CPAP use when compared to men without LUTS (26).…”
Section: Sleep and Lower Urinary Tract Symptomsmentioning
confidence: 99%
“…Moreover, one study also reported that BPH patients with storage symptoms were highly likely to have OSA [34]. In a study that evaluated the relationship between CPAP adherence and nocturia episodes in BPH patients, there was no significant relationship between the two [35]. It was assumed that disconnection of the mask because of nocturia would affect CPAP adherence, but that pattern was not as evident in BPH patients who perceived therapeutic benefits from CPAP therapy [35].…”
Section: Benign Prostate Hyperplasia: Relationship To Nocturia Sleepmentioning
confidence: 99%
“…Ocean circulation constitutes a major component of global surface heat transport (Ganachaud and Wunsch 2000) and, as such, plays a significant role in determining the Earth's climate. However, despite improvements in our understanding of the role of the oceans in climate, significant uncertainty remains regarding how the oceans behave as a climate feedback (Marshall et al 2015), particularly in the context of future climate predictions in response to anthropogenic forcings (e.g.…”
Section: Introductionmentioning
confidence: 99%